Perbuatan Melawan Hukum Terhadap Tindak Pidana Pengambilan Benda Bergerak Sebagai Objek Pembiayaan Leasing - Tito Alhafezt; Triono Eddy; Alpi Sahari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The principle of the pacta sun servanda agreement stating that the agreement made by the parties to the agreement, will be the law for both, remains in force and becomes the main hope in the law of the agreement. But the agreement that provides fiduciary guarantees under the hand cannot be executed. The execution process must be carried out by submitting a lawsuit to the Negri Court through normal procedural law so that the court's ruling decreases. This paper aims to analyze or examine the legal arrangements for the taking of movable objects as objects of leasing financing and criminal liability for the actions of taking movable objects as objects of leasing financing. The results of this study indicate that criminal policies against financial institutions in the execution of fiduciary guarantees by debt collectors who have changed hands under the law number 42 of 199 concerning fiduciary guarantees to ensure legal certainty are made akata by the notary public and registered with the fiduciary office. Law enforcement against leasing parties in withdrawing fiduciary collateral by debt collectors based on law number 42 of 1999 concerning fiduciary explains that the right of execution is the authority of the court, not the authority of the seller of debt collection services that are usually leased by the leasing party.